Social-Economics Implications of the Low Carbon Energy System - Kasavan S.; Mohammad N.; Siron R. (Springer Science and Business Media Deutschland GmbH, 2025)
Nowadays, providing energy for all communities in a sustainable way is one of the greatest global challenges. Natural gas has an essential part in the energy mix, and global energy supply transition as the world moves towards a low-carbon future. As the world?s population grows and more people move to cities, the power demand is growing. Energy firms must discover cost-effective alternatives, and some experts believe natural gas may play a significant role in this effort. Natural gas is the cleanest form of hydrocarbon and is abundant and flexible, aiding meet global energy demands. Reducing CO2 emissions and increasing air quality are universally recognized. Natural gas is not just reducing worldwide CO2 emissions; it provides less polluting and cleaner fuel to improve human health and mitigate environmental degradation. Natural gas helps move the world economy away from harmful energy sources. Natural gas also has considerable social and economic benefits. This book chapter has discussed the global trends of natural gas, the potential for natural gas as a substitute fuel, and the impacts of natural gas on social and economic aspects. The study discussion indicated that natural gas could play a significant role as a shift fuel in several ways, including replacing coal in power generation, substituting for other fuels in the various sectors, and facilitating the transition towards renewable energy systems. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.